Pengembangan Keterampilan Berbicara Siswa Sekolah Dasar Berbasis Pembelajaran Interaktif - Annisa, Nur; Hamzah, Rahma Ashari (Universitas Sulawesi Barat, 2025)
Speaking skills in elementary school play a crucial role in developing students’ communication skills and supporting their learning success in various fields. The purpose of this study was to analyze effective strategies and methods for developing elementary school students’ speaking skills. The method used was a literature review, reviewing various journals, books, and relevant research findings related to speaking instruction. The results showed that storytelling, show and tell, role-playing, and group discussions can improve students’ courage, fluency, and critical thinking skills. An interactive learning environment and teacher support as facilitators are also important factors in the successful development of speaking skills in elementary school